Recruiting specialized macrophages across the borders to restore brain functions - Corraliza, Inés (Frontiers in Cellular Neuroscience, 2014)
Although is well accepted that the central nervous system has an immune privilege protected by the blood brain barrier and maintained by the glia, it is also known that in homeostatic conditions, peripheral immune cells are able to penetrate to the deepest regions of brain without altering the structural integrity of the BBB. Nearly all neurological diseases, including degenerative, autoimmune or infectious ones, compromising brain functions, develop with a common pattern of inflammation in which macrophages and microglia activation have been regarded often as the “bad guys”. However, recognizing the huge heterogeneity of macrophage populations and also the different expression properties of microglia, there is increasing evidence of alternative conditions in which these cells, if primed and addressed in the correct direction, could be essential for reparative and regenerative functions. The main proposal of this review is to integrate studies about macrophage’s biology at the brain borders where the ultimate challenge is to penetrate through the BBB and contribute to change or even stop the course of disease. Thanks to the efforts made in the last century, this special wall is currently recognized as a highly regulated cooperative structure, in which their components form Neurovascular Units (NVU). This new scenario prompted us to review the precise cross-talk between the mind and body modes of immune response.